Bactericidal Efficacy of Silver Impregnated Activated Carbon for Disinfection of Water: Bactericidal Efficacy of Silver Impregnated Carbon (Biological Sciences - PJSIR, 2009)
When highly contaminated water was passed through two types of silver coated activated carbon and their mixtures with sand, the former was found to be far better medium for disinfection of water, with bactericidal efficacy of about 2.5 times that of the latter.